Myxoinflammatory Fibroblastic Sarcoma: A Radiographical, Pathological, and Immunohistochemical Report of Rare Malignancy - Michitaka Kato; Takuji Tanaka; Takatoshi Ohno (Case Reports in Orthopedics)
Myxoinflammatory fibroblastic sarcoma (MIFS) is a rare, painless, and intermediate (rarely metastasizing) fibroblastic tumor, which commonly occurs in the extremities, with an equal sex predilection. This sarcoma is composed of a mixed inflammatory infiltrate along with spindled, epithelioid, and bizarre tumor cells in a background of hyaline and myxoid areas. In spite of such a distinctive morphology, the tumor can be a diagnostic challenge, simulating inflammatory conditions as well as neoplastic nature. For accurate diagnosis, the tumor requires extensive clinical, radiological, and pathological investigations. We present a case of MIFS in a 19-year-old female who presented with a mass in the left ankle. After appropriate excision and postoperative radiation therapy, she is free of disease, including recurrence and metastasis, at 12 years postoperatively.